PESTS OF CARAGANA OF THE SOUTHERN COAST OF LAKE ISSYK-KUL - Kudaibergenova A. K.; Ishenbaeva S. T. (Vestnik Issyk-Kulʹskogo universiteta)
The article presents the environmental problem of some types of shrubs. The object of the study were shrubs growing in this area. For the region, shrubs play a huge role, since they perform soil protection, anti-mudflow and other functions. Wild bushes on the coast of Lake Issyk-Kul not only play an important ecological role as a biological filter for the lake, but also serve as a haven for various animals, thereby maintaining the natural biological diversity of the wild ecosystem. The increase in anthropogenic pressure on the shrub ecosystem has led to a decrease in their area and to a decrease in the natural regeneration of wild shrubs. In this regard, the purpose of our research was to study the condition of wild bushes on the coast of Lake. Issyk-Kul, subject to varying degrees of anthropogenic pressure. During field research in caragana thickets, a pest species that had not previously been found in this area was identified and identified. The article provides brief biological characteristics of the identified pest species. Based on field and laboratory studies, the authors propose further study of the caragana species and its pest, as well as proposed control measures, since caragana is of great economic importance in this region.